2016
DOI: 10.2807/1560-7917.es.2016.21.38.30343
|View full text |Cite
|
Sign up to set email alerts
|

Community-wide outbreak of haemolytic uraemic syndrome associated with Shiga toxin 2-producing Escherichia coli O26:H11 in southern Italy, summer 2013

Abstract: In summer 2013, an excess of paediatric cases of haemolytic uraemic syndrome (HUS) in a southern region of Italy prompted the investigation of a community-wide outbreak of Shiga toxin 2-producing Escherichia coli (STEC) O26:H11 infections. Case finding was based on testing patients with HUS or bloody diarrhoea for STEC infection by microbiological and serological methods. A case–control study was conducted to identify the source of the outbreak. STEC O26 infection was identified in 20 children (median age 17 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 29 publications
4
46
0
5
Order By: Relevance
“…In this study low frequency of STEC and EIEC (one infections was found We can hypothesize that our strains (diarrheal stool samples) analysedwere not related olitis and haemolytic uremic syndrome. Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3].…”
Section: Discussionsupporting
confidence: 80%
“…In this study low frequency of STEC and EIEC (one infections was found We can hypothesize that our strains (diarrheal stool samples) analysedwere not related olitis and haemolytic uremic syndrome. Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3].…”
Section: Discussionsupporting
confidence: 80%
“…(Grimont & Xavier-Weill, 2007), L. monocytogenes e STEC (Germinario et al, 2016). Tuttavia, ai fini epidemiologici, il potere discriminante di tale metodo è molto spesso insufficiente.…”
Section: Analisi Fenotipica E Molecolare Dei Ceppi Isolatiunclassified
“…Il primo si riferisce ad una vasta epidemia in comunità occorsa nell'estate 2013 in Puglia e connessa al probabile consumo di latticini contaminati che ha coinvolto 20 bambini, tutti con SEU (Germinario et al, 2016), da 7 dei quali è stato possibile isolare un ceppo STEC O26 (stx2+, eae+). L'analisi comparativa dei ceppi caratterizzati mediante PFGE mostrava diversi profili elettroforetici, suggerendo un possibile focolaio ad eziologia multipla (vedi oltre).…”
Section: Isolamenti DI Ceppi Stec Da Infezioni Umaneunclassified
See 2 more Smart Citations